2013
DOI: 10.1111/aos.12278
|View full text |Cite
|
Sign up to set email alerts
|

Marked reductions in visual impairment due to diabetic retinopathy achieved by efficient screening and timely treatment

Abstract: ABSTRACT.Purpose: Diabetic retinopathy (DR) is the most common complication of diabetes and needs to be diagnosed early to prevent severe sight-threatening retinopathy. Digital photography with telemedicine connections is a novel way to deliver cost-effective, accessible screening to remote areas. Screening for DR in a mobile eye examination unit (EyeMo) is compared to traditional service models (i.e. local municipal services or a commercial service provider). The quality of images, delays from screening to tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 19 publications
2
57
0
5
Order By: Relevance
“…Being highly sensitive and specific for detecting both early and referable DR, it has been shown to increase access to screening and proven to be cost-effective in community screening programmes 71–76. Recently, RP has also been increasingly applied in the field of teleophthalmology, especially in areas with limited resources and poor access to eye care, achieving significant reductions in DR-related visual impairment 18 77 78. In the event that RP is unavailable or images are unreadable, ophthalmoscopy can be used as an alternative for screening 79 80…”
Section: Discussionmentioning
confidence: 99%
“…Being highly sensitive and specific for detecting both early and referable DR, it has been shown to increase access to screening and proven to be cost-effective in community screening programmes 71–76. Recently, RP has also been increasingly applied in the field of teleophthalmology, especially in areas with limited resources and poor access to eye care, achieving significant reductions in DR-related visual impairment 18 77 78. In the event that RP is unavailable or images are unreadable, ophthalmoscopy can be used as an alternative for screening 79 80…”
Section: Discussionmentioning
confidence: 99%
“…32,33 A marked decrease in diabetic retinopathy related visual impairment can be achieved through screening and timely treatment. 34 However, the capacity of the health system to confront the disease should be considered before screening. A study conducted by Hashemi et al in rural areas in the north of Iran showed that diagnostic facilities did not improve in rural areas in the past decades and these areas even lacked minimum facilities and equipment for the treatment of ocular problems.…”
Section: Discussionmentioning
confidence: 99%
“…18 Similar screening workflows have been adopted in several other European nations also keen to reduce DR-related blindness. [9][10][11] In addition, automated screening algorithms have begun to be incorporated into the national DR screening program in Scotland, UK. 19 These offer the potential to screen out the bulk of healthy, and most time consuming to assess, images before a human retinal screener needs to be involved.…”
Section: Development Of the Diabetic Retinopathy Screening Workflowmentioning
confidence: 99%